Proses Produksi Beton Segar Pada Mesin Batching Plant di PT Prima Beton Nusantara - Rifqi Wafi Fathullah; Viktor Naubnome; Iwan Nugraha Gusniar (Peneliti.net, 2022)
The purpose of this study was to obtain the results of the Fresh Concrete Production Process at the Batching Plant Machine at PT Prima Beton Nusantara. Concrete production process at PT. The SBU Prima Beton is a production that is quite widely used by other PTs. From the report above, several conclusions can be drawn, namely: 1) The concrete production process using a batching plant machine is the thing that is most widely used by companies that make large amounts of concrete because of its efficiency. which is quite good and fast., 2) The stirring process is one of the main things in the process of making concrete., 3) The production process using the Batcing Plant Machine is enough to affect the quality of the concrete produced.